Endocrine Regulation of Lifespan in Insect Diapause - Hutfilz, Corinne (Frontiers in Physiology, 2022)
Diapause is a physiological adaptation to conditions that are unfavorable for growth or reproduction. During diapause, animals become long-lived, stress-resistant, developmentally static, and non-reproductive, in the case of diapausing adults. Diapause has been observed at all developmental stages in both vertebrates and invertebrates. In adults, diapause traits weaken into adaptations such as “hibernation,” “dormancy,” or “torpor,” which represent evolutionarily diverse versions of the traditional diapause traits. These traits are regulated through modifications of the endocrine program guiding development. While much work has been done to characterize these modifications, the interactions between hormones and their downstream consequences are incompletely understood. The current state of diapause endocrinology is reviewed here to highlight the relevance of diapause beyond its use as a model to study seasonality and development. Specifically, insect diapause is an emerging model to study mechanisms that determine lifespan. The induction of diapause represents a dramatic change in the normal progression of age. Hormones such as juvenile hormone, 20-hydroxyecdysone, and prothoracicotropic hormone are well-known to modulate this plasticity. The induction of diapause—and by extension, the cessation of normal aging—is coordinated by interactions between these pathways. However, research directly connecting diapause endocrinology to the biology of aging is lacking. This review explores connections between diapause and aging through the perspective of endocrine signaling. The current state of research in both fields suggests appreciable overlap that will greatly contribute to our understanding of diapause and lifespan determination.